A freeze-thaw and hydrolysis-resistant ASA papermaking sizing agent emulsion and preparation method thereof

By using an ultraviolet initiator for ASA glue emulsion in an alkenyl succinic anhydride sizing agent, combined with nanocellulose crystals (CNCs), the unstable emulsion problem caused by traditional ultraviolet initiators is solved, and the preparation of ASA glue emulsion that is anti-freeze-thaw and hydrolysis is achieved.

CN116836304BActive Publication Date: 2025-03-25QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310959796.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2025-03-25
Estimated Expiration
2043-08-02

AI Technical Summary

Technical Problem

Traditional UV initiators may lead to unstable emulsions during the preparation of alkenyl succinic anhydride sizing agents, affecting product performance.

Method used

An ultraviolet initiator for ASA glue sizing emulsion was used to produce (2,4,6-trimethylbenzoyl)phenyl-phenylphosphinyl chloride by reaction in the presence of triethylamine, and then react with 2-hydroxyethyl isocyanate to obtain IETMBPP, and combined with nanocellulose crystals (CNC) to form CNC/IETMBPP particles, which were used to emulsify and stabilize the ASA emulsion and initiate monomer molecular polymerization under ultraviolet light.

Benefits of technology

The ASA emulsion is emulsified under ultraviolet light to form an ASA glue emulsion that is anti-freeze-thaw and hydrolysis-resistant ASA glue emulsion. The preparation method is simple and does not require complex chemical modifications and high-cost additives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116836304B_ABST
    Figure CN116836304B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing an alkenyl succinic anhydride sizing agent emulsion: CNC / IETMBPP particles are uniformly dispersed in water as a water phase; ASA is mixed with the water phase and emulsified to obtain a first emulsion; acrylamide and methacrylic acid are added to the first emulsion, and the emulsification is performed again under ultraviolet light irradiation to obtain the first emulsion. The preparation method is simple and does not require complex chemical modification and the addition of high-cost additives; in addition, the ultraviolet light-induced cross-linking polymerization technology has the advantages of being environmentally friendly and having a fast reaction rate; at the same time, the prepared ASA sizing agent emulsion has a long frozen shelf life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material chemistry, and in particular relates to a freeze-thaw and hydrolysis-resistant ASA papermaking sizing agent emulsion and a preparation method thereof. Background Art

[0002] In recent years, UV-induced cross-linking polymerization technology has received extensive attention in the field of polymer material preparation. Through the action of UV-initiators, rapid cross-linking and curing of polymer materials can be achieved, which has the advantages of simple operation, fast reaction rate, and environmental friendliness. However, traditional UV-initiators may cause unstable emulsions in the preparation process of alkenyl succinic anhydride sizing agents, thereby affecting the performance of the products. Therefore, it is of great significance to develop a UV-initiator suitable for the preparation of alkenyl succinic anhydride sizing agents.

[0003] Nanocrystalline cellulose (CNC) is a bio-based polymer material with excellent mechanical properties, biocompatibility and biodegradability. It has received extensive attention in the field of polymer materials. Combining nanocellulose with other functional materials can give full play to its UV-induced cross-linking polymerization technology in various fields, which has received extensive attention in the field of polymer material preparation in recent years. Summary of the invention

[0004] Aiming at the problem that the current ultraviolet initiator causes the instability of alkenyl succinic anhydride sizing agent, the present invention provides an ultraviolet initiator for ASA sizing agent emulsion and a preparation method thereof, which can initiate monomer molecular polymerization under ultraviolet light on the basis of emulsified stable ASA emulsion to obtain freeze-thaw-resistant and hydrolysis-resistant ASA sizing agent emulsion.

[0005] The invention also provides an ASA sizing agent emulsion prepared by using the ultraviolet initiator, which has good antifreeze performance.

[0006] To achieve the above purpose, the present invention adopts the following technical solution.

[0007] A method for preparing an ultraviolet initiator for an ASA sizing agent emulsion comprises the following steps:

[0008] (1) 2,4,6-trimethylbenzoyl chloride and diphenylphosphinoyl chloride react in a solvent in the presence of triethylamine under a protective atmosphere, and (2,4,6-trimethylbenzoyl)phenyl-phenylphosphinoyl chloride is separated and purified;

[0009] (2) dissolving (2,4,6-trimethylbenzoyl)phenyl-phenylphosphinyl chloride in anhydrous tetrahydrofuran (THF) and stirring evenly to obtain solution A;

[0010] Dissolve 2-hydroxyethyl isocyanate in anhydrous dichloromethane (DCM) and stir well to obtain solution B;

[0011] The solution B is slowly added dropwise to the obtained solution A under stirring conditions for reaction. After the reaction is completed, the residual solvent is removed, and the residue is extracted with petroleum ether and water to separate the organic phase; the organic phase is dehydrated and the solvent is removed to obtain 2-[(2,4,6-trimethylbenzoyl)phenyl-phenylphosphinate]ethyl isocyanate, referred to as IETMBPP;

[0012] (3) IETMBPP was dissolved in anhydrous ethanol, and then nanocellulose crystals (CNC) were added. After ultrasonic reaction, the mixture was allowed to stand for solid-liquid separation to obtain a precipitate, which was washed with anhydrous ethanol and dried to obtain CNC / IETMBPP particles.

[0013] In step (1), the solvent is selected from tetrahydrofuran, N,N-dimethylformamide or dichloromethane.

[0014] In step (1), the separation and purification step is as follows: an equal volume of THF is added to the reaction system, and then an equal volume of saturated sodium chloride solution is added, the mixture is stirred and allowed to stand for stratification, the organic phase is collected and dried by adding sodium sulfate, the THF is evaporated off in vacuo after filtration to obtain a crude product, which is then dissolved and crystallized with n-hexane.

[0015] In step (2), the mass ratio of (2,4,6-trimethylbenzoyl)phenyl-phenylphosphinyl chloride to THF is 1:5-20; more preferably 1:10.

[0016] In step (2), the mass ratio of 2-hydroxyethyl isocyanate to DCM is 1:1-20, and more preferably 1:10.

[0017] In step (2), the mass ratio of solution A to solution B is 1:1-1:5, more preferably 1:3.

[0018] In step (3), the mass ratio of IETMBPP to anhydrous ethanol is 1:5-20; more preferably 1:10.

[0019] In step (3), the mass ratio of IETMBPP to CNC is 1:10-50; more preferably 1:25.

[0020] A UV initiator obtained by the above preparation method.

[0021] The application of the above-mentioned ultraviolet initiator in the preparation of ASA sizing agent emulsion.

[0022] A method for preparing a freeze-thaw and hydrolysis-resistant ASA papermaking sizing agent emulsion comprises the following steps:

[0023] S1: CNC / IETMBPP particles are uniformly dispersed in water as the aqueous phase; alkenyl succinic anhydride (ASA) is mixed with the aqueous phase and emulsified to obtain a first emulsion;

[0024] S2: Add acrylamide (AAm) and methacrylic acid (MAAc) to the first emulsion, and emulsify it again under ultraviolet light to obtain the second emulsion, i.e., the freeze-thaw and hydrolysis-resistant ASA sizing agent emulsion.

[0025] In step S1, the mass fraction of the CNC / IETMBPP aqueous dispersion is 0.1wt%-2wt%; more preferably 1.0wt%.

[0026] In step S1, the mass ratio of the aqueous phase to ASA is 10:1-1:4; more preferably 1:2;

[0027] In step S2, the mass ratio of AAm to MAAc is 1:1-1:5, and more preferably 1:2.

[0028] In step S2, the mass fraction of AAm in the aqueous phase is 1 wt%-10 wt%; more preferably 3 wt%.

[0029] In the above steps, the emulsification method can be ultrasonic emulsification or shear emulsification.

[0030] An ASA paper sizing agent emulsion prepared by the above method has an average particle size of 1.7-6.0 μm in droplets, and the emulsion can remain stable at at least -20°C, and can still maintain the original sizing performance after freeze-thaw treatment after 30 days.

[0031] The mechanism of the present invention is as follows:

[0032] IETMBPP can be obtained by the nucleophilic substitution reaction of (2,4,6-trimethylbenzoyl)phenyl-phenylphosphinyl chloride with 2-hydroxyethyl isocyanate: the chlorine atom of phosphinyl chloride is replaced by the alkoxide ion derived from 2-hydroxyethyl isocyanate, and then separated and purified by recrystallization or column chromatography.

[0033] The isocyanate groups (-NCO) in the IETMBPP molecule can react with the hydroxyl groups (-OH) present on the CNC surface. This reaction forms a covalent urethane bond (-NHCOO-) between IETMBPP and CNC, fixing IETMBPP on the CNC surface.

[0034] In the presence of ultraviolet (UV) light, the phosphinate part of the photoinitiator undergoes homolysis to produce highly active free radicals that can initiate the polymerization of AAm and MAAc. The phosphinate free radical can extract a hydrogen atom from AAm and MAAc to form a new polymer free radical to propagate the polymerization reaction.

[0035] Phosphinate radical + AAm / MAAc → polymer radical

[0036] The polymer radicals react with other AAm and MAAc molecules to form a P(AAm / MAAc) polymer network.

[0037] Since the photoinitiator is covalently bound to CNC, the polymerization process will preferentially occur near the CNC surface, forming a P(AAm / MAAc) gel layer around the CNC particles.

[0038] IETMBPP can be used as a bifunctional photoinitiator: the carboxyl group allows covalent connection with CNC, thus having the effect of emulsifying and stabilizing ASA; when the AAm and MAAc gathered around CNC / IETMBPP at the oil-water interface are irradiated with ultraviolet light, the IETMBPP residues initiate the polymerization of AAm and MAAc, forming a gel layer that is resistant to freeze-thaw and water molecule penetration, and further prevents water molecules from crossing the interface particles into the oil phase at low temperatures, thereby producing the anti-hydrolysis property of ASA.

[0039] The present invention has the following advantages:

[0040] The present invention adopts CNC / IETMBPP as an ASA emulsion emulsifier and can also be used as an ultraviolet light initiator to make droplets form an AAm / MAAc hydrogel layer at the oil-water interface, which can effectively improve the hydrolysis resistance and freeze-thaw resistance of the alkenyl succinic anhydride sizing agent; the preparation method is simple and does not require complex chemical modification and the addition of high-cost additives; in addition, the ultraviolet light-initiated cross-linking polymerization technology has the advantages of being environmentally friendly and having a fast reaction rate; at the same time, the prepared ASA sizing agent emulsion has a very long frozen shelf life. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 is an atomic force micrograph of the CNC / IETMBPP particles in Example 1;

[0042] Figure 2 is a microscopic picture of the hydrolysis-resistant and freeze-thaw-resistant ASA sizing agent emulsion prepared in Example 4;

[0043] Figure 3 It is the appearance picture of the ASA sizing agent emulsion prepared in Example 4 before and after freeze-thaw. DETAILED DESCRIPTION

[0044] The present invention is further described below in conjunction with embodiments and drawings, but the present invention is not limited by the following embodiments.

[0045] Example 1 Preparation of UV Initiator for ASA Sizing Agent Emulsion

[0046] (1) Preparation of (2,4,6-trimethylbenzoyl)phenyl-phenylphosphinyl chloride:

[0047]

[0048] Under nitrogen protection, 2,4,6-trimethylbenzoyl chloride (1.2 eq) and diphenylphosphinoyl chloride (1 eq) were dissolved in tetrahydrofuran (THF), and triethylamine was added as an acid-binding agent to react. An equal volume of THF was added to the reaction system, and then an equal volume of saturated sodium chloride solution was added. After stirring, the mixture was allowed to stand for stratification. The organic phase was collected and dried by adding sodium sulfate. After filtering, THF was evaporated in vacuo to obtain a crude product, which was then dissolved and crystallized with n-hexane. After crystallization and drying, (2,4,6-trimethylbenzoyl)phenyl-phenylphosphinoyl chloride was obtained.

[0049] (2) Preparation of IETMBPP:

[0050]

[0051] Solution A was prepared by mixing 1 part of (2,4,6-trimethylbenzoyl)phenyl-phenylphosphinyl chloride with 5 parts of THF and stirring evenly; Solution B was prepared by dissolving 1 part of 2-hydroxyethyl isocyanate in 1 part of dichloromethane (DCM); and stirring evenly.

[0052] One portion of solution B was slowly added dropwise to one portion of solution A while stirring. After the addition was completed, the reaction was continued with stirring for 24 hours. After the reaction was completed, the solvent was removed by distillation. The residue was extracted with petroleum ether and water, the organic phase was separated, the organic phase was dehydrated with anhydrous sodium sulfate, and finally the solvent was distilled off to collect IETMBPP particles.

[0053] The infrared spectrum of IETMBPP shows that its characteristic peaks include:

[0054] 2250-2270 cm -1 : The stretching vibration of N=C=O indicates the presence of isocyanate group;

[0055] 1710-1720 cm -1 : Stretching vibration of amide (C=O), indicating the presence of amide group;

[0056] 1600-1620 cm -1 : Stretching vibration of the aromatic ring (C=C), indicating the presence of 2,4,6-trimethylbenzoylphenyl;

[0057] 1250-1260 cm -1 : The stretching vibration of P=O indicates the presence of phosphinate groups;

[0058] 1090-1150 cm -1 : Stretching vibration of POC, indicating the presence of phosphinate groups;

[0059] 3000-3100 cm-1 : The CH stretching vibration on the aromatic ring indicates the existence of the aromatic ring.

[0060] Its hydrogen spectrum, carbon spectrum, and phosphorus spectrum NMR spectra show:

[0061] 1 H-NMR (400 MHz, CDCl3):

[0062] δ 1.20-1.40 (t, 3H, J ≈ 7 Hz): hydrogen atom of methyl (CH3) on ethyl ester group;

[0063] δ 3.40-3.60 (q, 2H, J ≈ 7 Hz): hydrogen atom of the methane group (CH2) on the ethoxylated group;

[0064] δ 6.90-7.10 (m, 2H): hydrogen atoms on the benzene ring that are not adjacent to the methyl group;

[0065] δ 7.20-7.40 (m, 1H): hydrogen atom adjacent to the methyl group on the benzene ring;

[0066] δ 2.20-2.40 (s, 9H): three methyl (CH3) hydrogen atoms.

[0067] 13 C-NMR (100 MHz, CDCl3):

[0068] δ 14.0-16.0: methyl (CH3) carbon atom on the ethyl ester group;

[0069] δ 58.0-62.0: carbon atom of the methane group (CH2) on the ethyl ester group;

[0070] δ 127.0-131.0: carbon atoms on the benzene ring that are not adjacent to the methyl group;

[0071] δ 135.0-139.0: carbon atom adjacent to the methyl group on the benzene ring;

[0072] δ 21.0-23.0: three methyl (CH3) carbon atoms;

[0073] δ 163.0-167.0: amide (C=O) carbon atom;

[0074] δ 165.0-169.0: Phosphinate group (P=O) carbon atom.

[0075] 31 P-NMR (162 MHz, CDCl3):

[0076] δ 30.0-34.0: Phosphinate group (P=O) phosphorus atom.

[0077] The structure of 2-isocyanate ethyl 2,4,6-trimethylbenzoylphenylphosphinate can be confirmed by the characteristic peaks of infrared spectrum and nuclear magnetic resonance spectrum.

[0078] (3) Preparation of CNC / IETMBPP composite particles:

[0079] 1 part of the prepared IETMBPP was dissolved in 5 parts of anhydrous ethanol and stirred evenly, then 10 parts of CNC were added, and the mixed solution was ultrasonically treated using an ultrasonic stirrer for about 30 minutes to ensure that the nanocellulose crystals were fully dispersed and combined, and the solution was allowed to stand to allow the composite particles to precipitate, the precipitate was filtered out, and then washed with anhydrous ethanol for 2-3 times, and finally the composite particles were dried to constant weight using a vacuum dryer to obtain CNC / IETMBPP composite particles ( Figure 1 ).

[0080] Example 2 Preparation of UV Initiator for ASA Sizing Agent Emulsion

[0081] (1) Preparation of (2,4,6-trimethylbenzoyl)phenyl-phenylphosphinyl chloride:

[0082] Under nitrogen protection, 2,4,6-trimethylbenzoyl chloride (1.5 eq) and diphenylphosphinoyl chloride (1 eq) were dissolved in tetrahydrofuran (THF), and triethylamine was added as an acid-binding agent to react. An equal volume of THF was added to the reaction system, and then an equal volume of saturated sodium chloride solution was added. After stirring, the mixture was allowed to stand for stratification. The organic phase was collected and dried by adding sodium sulfate. After filtering, THF was evaporated in vacuo to obtain a crude product, which was then dissolved and crystallized with n-hexane. After crystallization and drying, (2,4,6-trimethylbenzoyl)phenyl-phenylphosphinoyl chloride was obtained.

[0083] (2) Preparation of IETMBPP:

[0084] 1 part of (2,4,6-trimethylbenzoyl)phenyl-phenylphosphinyl chloride was mixed with 10 parts of THF and stirred to prepare solution A; 1 part of 2-hydroxyethyl isocyanate was dissolved in 10 parts of DCM solvent and stirred to obtain solution B;

[0085] Three portions of solution B were slowly added dropwise to one portion of solution A while stirring. After the addition was completed, the reaction was continued with stirring for 24 hours. After the reaction was completed, the solvent was removed by distillation. The residue was extracted with petroleum ether and water, the organic phase was separated, the organic phase was dehydrated with anhydrous sodium sulfate, and finally the solvent was distilled off to collect IETMBPP particles.

[0086] (3) Preparation of CNC / IETMBPP composite particles:

[0087] 1 part of the prepared IETMBPP was dissolved in 10 parts of anhydrous ethanol and stirred evenly, then 25 parts of CNC were added, and the mixed solution was ultrasonically treated using an ultrasonic stirrer for about 30 minutes to ensure that the nanocellulose crystals were fully dispersed and combined, and the solution was allowed to stand to allow the composite particles to precipitate, the precipitate was filtered out, and then washed with anhydrous ethanol 2-3 times, and finally the composite particles were dried to constant weight using a vacuum dryer to obtain CNC / IETMBPP composite particles.

[0088] Example 3 Preparation of UV Initiator for ASA Sizing Agent Emulsion

[0089] (1) Preparation of (2,4,6-trimethylbenzoyl)phenyl-phenylphosphinyl chloride:

[0090] Under nitrogen protection, 2,4,6-trimethylbenzoyl chloride (1.2 eq) and diphenylphosphinoyl chloride (1 eq) were dissolved in tetrahydrofuran (THF), and triethylamine was added as an acid-binding agent to react. An equal volume of THF was added to the reaction system, and then an equal volume of saturated sodium chloride solution was added. After stirring, the mixture was allowed to stand for stratification. The organic phase was collected and dried by adding sodium sulfate. After filtering, THF was evaporated in vacuo to obtain a crude product, which was then dissolved and crystallized with n-hexane. After crystallization and drying, (2,4,6-trimethylbenzoyl)phenyl-phenylphosphinoyl chloride was obtained.

[0091] (2) Preparation of IETMBPP:

[0092] 1 part of 4-(2,4,6-trimethylbenzoyl)phenyl-phenylphosphinyl chloride was mixed with 20 parts of THF and stirred to prepare solution A; 1 part of 2-hydroxyethyl isocyanate was dissolved in 20 parts of DCM solvent and stirred to obtain solution B;

[0093] 5 portions of solution B were slowly added dropwise to 1 portion of solution A while stirring. After the addition was completed, the reaction was continued with stirring for 24 hours. After the reaction was completed, the solvent was removed by distillation. The residue was extracted with petroleum ether and water, the organic phase was separated, the organic phase was dehydrated with anhydrous sodium sulfate, and finally the solvent was distilled off to collect IETMBPP particles.

[0094] (3) Preparation of CNC / IETMBPP composite particles:

[0095] 1 part of the prepared IETMBPP was dissolved in 20 parts of anhydrous ethanol and stirred evenly, then 50 parts of CNC were added, and the mixed solution was ultrasonically treated using an ultrasonic stirrer for about 30 minutes to ensure that the nanocellulose crystals were fully dispersed and combined. The solution was allowed to stand to allow the composite particles to precipitate, the precipitate was filtered out, and then washed with anhydrous ethanol 2-3 times. Finally, the composite particles were dried to constant weight using a vacuum dryer to obtain CNC / IETMBPP composite particles.

[0096] Example 4 Preparation of ASA sizing agent emulsion

[0097] The CNC / IETMBPP obtained in Example 1 was dispersed in water to prepare a water dispersion with a mass fraction of 0.1 wt%, and stirred evenly to serve as the water phase; 10 parts of the water phase were mixed with 1 part of ASA, and after the first emulsification to obtain a uniform emulsion, 0.02 parts of AAm and 0.02 parts of MAAc were added respectively, and the second emulsification was continued under ultraviolet light to obtain a freeze-thaw and hydrolysis-resistant ASA papermaking sizing emulsion ( Figure 2 ).

[0098] Example 5 Preparation of ASA sizing agent emulsion

[0099] The CNC / IETMBPP obtained in Example 2 was dispersed in water to form an aqueous dispersion with a mass fraction of 1.0 wt%, and stirred evenly to form an aqueous phase; 1 part of the aqueous phase was mixed with 2 parts of ASA, and after the first emulsification to obtain a uniform emulsion, 0.03 parts of AAm and 0.06 parts of MAAc were added respectively, and the second emulsification was continued under ultraviolet light to obtain a freeze-thaw and hydrolysis-resistant ASA papermaking sizing emulsion.

[0100] Example 6 Preparation of ASA sizing agent emulsion

[0101] The CNC / IETMBPP obtained in Example 3 was dispersed in water to form an aqueous dispersion with a mass fraction of 2.0 wt%, and stirred evenly to form an aqueous phase; 1 part of the aqueous phase was mixed with 4 parts of ASA, and after the first emulsification to obtain a uniform emulsion, 0.1 parts of AAm and 0.5 parts of MAAc were added respectively, and the second emulsification was continued under ultraviolet light to obtain a freeze-thaw and hydrolysis-resistant ASA papermaking sizing emulsion.

[0102] Application Example 1 Application of ASA sizing agent emulsion in papermaking

[0103] The sizing was carried out by the in-slurry sizing method. Before sizing, the ASA composite papermaking sizing agent emulsion was diluted to 0.5%, the pulp concentration was adjusted to 1%, and 1% aluminum sulfate (relative to the mass percentage of absolute dry pulp) was added to the pulp at a stirring rate of 1000rpm. Then, the pH value of the pulp was adjusted to 7-8.5 with a 1 mol / L sodium hydroxide solution, and then the diluted ASA sizing agent emulsion (dosage of 0.15%, the total mass of ASA relative to the total mass of absolute dry pulp) and 0.03% (relative to the mass percentage of absolute dry pulp) of cationic polyacrylamide were added in sequence, and then stirred with a stirrer at a shear rate of 1000rpm for 2 minutes, and then allowed to stand for 30 seconds, and then a PTI paper sheet maker (model: RK3AKWT, origin: Austria) was used to make a hand sheet, and the hand sheet was 60g / m 2 (T205 om-88, TAPPI), the papermaking system is in accordance with ISO5289 / 2 and DIN54358 standards, and the Kaiser method manual papermaking mode is selected for papermaking. The papermaking hand sheet is dried at 105℃, and then the paper moisture is balanced at room temperature for 24 hours, and the ambient humidity is 50%.

[0104] The sizing performance is evaluated by measuring the sizing degree of papermaking paper (GB / T5405-2002). Before the measurement, the paper is cut into 30×30mm square pieces and placed in an environment of 25℃ and 50% humidity to balance the moisture for 24 hours. The four sides of the paper are folded to form a boat-shaped structure with a bottom area of ​​about 20×20mm, and then floated in a dilute solution of ammonium thiocyanate with a concentration of 2%. A drop of 0.5μL of 1% ferric chloride solution is dropped on the upper part of the boat-shaped paper with a rubber-tipped dropper, and a stopwatch is used to time. When a red spot appears in the middle of the ferric chloride droplet, the timing ends, and the time is the sizing degree of the paper sample. The front and back sides of the test sample are measured 10 times each, and the average value is taken.

[0105] The particle size statistics software provided by the optical microscope was used to count the diameters of 100 emulsion droplets observed under the microscope, and the average value was taken, which was the average particle size of the droplets.

[0106] Table 1 Performance of different sizing agents

[0107]

[0108] According to Table 1, the average droplet size of the ASA emulsion prepared by the present invention is relatively small, and the emulsion is placed at -20°C for 30 days without any phase precipitation and demulsification, indicating that the ASA emulsion prepared by the present invention has good stability. When the dosage is 0.15% (mass ratio of ASA to absolute dry pulp), the sizing degree of the paper sheet of the pulp-sizing paper is 439-522 seconds, indicating that the sizing performance of the emulsion is excellent, and the sizing degree of the sizing paper is still very high when the emulsion is used after being stored for 30 days, indicating that the emulsion has good anti-hydrolysis performance. During low-temperature frozen storage, due to the protection of the Amm / MAAc antifreeze gel layer, the emulsion has obvious anti-freeze-thaw and anti-hydrolysis properties. Under the freeze-thaw cycle conditions of -20°C and 80°C, the appearance does not change ( Figure 3 ).

Claims

1. A method for preparing an ultraviolet initiator for an ASA sizing agent emulsion, characterized in that: The following steps are involved: (1) 2,4,6-trimethylbenzoyl chloride and diphenylphosphinoyl chloride react in a solvent in the presence of triethylamine under a protective atmosphere, and (2,4,6-trimethylbenzoyl)phenyl-phenylphosphinoyl chloride is separated and purified; (2) dissolving (2,4,6-trimethylbenzoyl)phenyl-phenylphosphinyl chloride in anhydrous THF and stirring evenly to obtain solution A; Dissolve 2-hydroxyethyl isocyanate in anhydrous DCM and stir well to obtain solution B; The solution B is slowly added dropwise to the obtained solution A under stirring conditions for reaction. After the reaction is completed, the residual solvent is removed, and the residue is extracted with petroleum ether and water to separate the organic phase; the organic phase is dehydrated and the solvent is removed to obtain IETMBPP; (3) IETMBPP was dissolved in anhydrous ethanol, and then CNC was added. After ultrasonic reaction, the mixture was allowed to stand for solid-liquid separation to obtain a precipitate, which was washed with anhydrous ethanol and dried to obtain CNC / IETMBPP particles.

2. The preparation method according to claim 1, characterized in that: In step (1), the solvent is selected from tetrahydrofuran, N,N-dimethylformamide or dichloromethane.

3. The preparation method according to claim 1, characterized in that: In step (1), the separation and purification step is as follows: an equal volume of THF is added to the reaction system, and then an equal volume of saturated sodium chloride solution is added, the mixture is stirred and allowed to stand for stratification, the organic phase is collected and dried by adding sodium sulfate, the THF is evaporated off in vacuo after filtration to obtain a crude product, which is then dissolved and crystallized with n-hexane.

4. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of (2,4,6-trimethylbenzoyl)phenyl-phenylphosphinyl chloride to THF is 1:5-20; the mass ratio of 2-hydroxyethyl isocyanate to DCM is 1:1-20; the mass ratio of solution A to solution B is 1:1-1:5; In step (3), the mass ratio of IETMBPP to anhydrous ethanol is 1:5-20; in step (3), the mass ratio of IETMBPP to CNC is 1:10-50.

5. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of (2,4,6-trimethylbenzoyl)phenyl-phenylphosphinyl chloride to THF is 1:10; the mass ratio of 2-hydroxyethyl isocyanate to DCM is 1:10; the mass ratio of solution A to solution B is 1:3; In step (3), the mass ratio of IETMBPP to anhydrous ethanol is 1:10; the mass ratio of IETMBPP to CNC is 1:

25.

6. An ultraviolet initiator obtained by the preparation method according to any one of claims 1 to 5.

7. Use of the ultraviolet initiator according to claim 6 in preparing an ASA sizing agent emulsion.

8. A method for preparing a freeze-thaw and hydrolysis-resistant ASA paper sizing agent emulsion, characterized in that: The following steps are involved: S1: uniformly dispersing the ultraviolet initiator described in claim 6 into water as an aqueous phase; mixing ASA with the aqueous phase and emulsifying to obtain a first emulsion; S2: AAm and MAAc are added to the first emulsion, and the mixture is emulsified again under ultraviolet light to obtain a second emulsion, i.e., a freeze-thaw and hydrolysis-resistant ASA sizing agent emulsion.

9. The preparation method according to claim 8, characterized in that: In step S1, the mass fraction of the CNC / IETMBPP aqueous dispersion is 0.1wt%-2wt%; the mass ratio of the aqueous phase to ASA is 10:1-1:4; In step S2, the mass ratio of AAm to MAAc is 1:1-1:5; the mass fraction of AAm in the aqueous phase is 1wt%-10wt%; The emulsification method is selected from ultrasonic emulsification or shear emulsification.

10. The preparation method according to claim 8, characterized in that: In step S1, the mass fraction of the CNC / IETMBPP aqueous dispersion is 1.0wt%; the mass ratio of the aqueous phase to ASA is 1:2; In step S2, the mass ratio of AAm to MAAc is 1:2; the mass fraction of AAm in the aqueous phase is 3 wt%.

11. An ASA paper sizing agent emulsion obtained by the preparation method according to any one of claims 8 to 10, characterized in that: The average droplet size was 1.7-6.0 μm and the emulsion remained stable at -20 °C for at least 30 days.

Citation Information

Patent Citations

  • Alkenyl succinic anhydride paper sizing agent emulsion and preparation method and application thereof

    AU2020102641A4

  • Paper-based functional material for oil-water separation, preparation method and application thereof

    CN111218853A